Alginate degrading enzymes: an updated comprehensive review of the structure, catalytic mechanism, modification method and applications of alginate lyases. (18th August 2021) - Li, Qian; Zheng, Ling; Guo, Zilong; Tang, Tiancheng; Zhu, Benwei
Abstract: Alginate, a kind of linear acidic polysaccharide, consists of α-L-guluronate (G) and β-D-mannuronate (M). Both alginate and its degradation products (alginate oligosaccharides) possess abundant biological activities such as antioxidant activity, antitumor activity, and antimicrobial activity. Therefore, alginate and alginate oligosaccharides have great value in food, pharmaceutical, and agricultural fields. Alginate lyase can degrade alginate into alginate oligosaccharides via the β-elimination reaction. It plays an important role in marine carbon recycling and the deep utilization of brown algae. Elucidating the structural features of alginate lyase can improve our knowledge of its catalytic mechanisms. With the development of structural analysis techniques, increasing numbers of alginate lyases have been characterized at the structural level. Hence, it is essential and helpful to summarize and discuss the up-to-date findings. In this review, we have summarized progress on the structural features and the catalytic mechanisms of alginate lyases. Furthermore, the molecular modification strategies and the applications of alginate lyases have also been discussed. This comprehensive information should be helpful to expand the applications of alginate lyases.